1995
DOI: 10.1039/c39950001375
|View full text |Cite
|
Sign up to set email alerts
|

Complete retention of configuration in the nucleophilic substitution of 1-phenylbenzo[b]thiophenium salts by alkoxide anions

Abstract: Reaction of 1,2,3-triarylbenzo[b]thiophenium salts with alkoxide anions results in the exclusive formation of (2) alkoxy-substituted alkenes, indicating that the nucleophilic ring-opening reaction proceeds with complete retention of configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We have found that the 1-phenyl-1-benzothiophenium salts undergo nucleophilic substitution to lead to ring-opened alkenes or dephenylation products . The crystal structure of 1-phenyl-1-benzothiophenium triflate 5 reveals that the stereochemistry around the sulfur atom is tetrahedral and the short CC double bond length (1.308 Å) of the thiophene ring is within the observed range of the CC double bond length (1.30−1.37 Å) in arylethene systems.…”
mentioning
confidence: 85%
“…We have found that the 1-phenyl-1-benzothiophenium salts undergo nucleophilic substitution to lead to ring-opened alkenes or dephenylation products . The crystal structure of 1-phenyl-1-benzothiophenium triflate 5 reveals that the stereochemistry around the sulfur atom is tetrahedral and the short CC double bond length (1.308 Å) of the thiophene ring is within the observed range of the CC double bond length (1.30−1.37 Å) in arylethene systems.…”
mentioning
confidence: 85%
“…Cyclic sulfonium salts also react with many reagents, mostly nucleophiles . Because 1-alkyl-1-benzothiophenium salts are much higher in chemical reactivity than the corresponding 1-phenyl-1-benzothiophenium salts, the cycloadducts, 1-phenyl-2,3-dihydro-1-benzothiophenium salts, are expected to be more reactive. Previously, we reported that 1-aryl-1-benzothiophenium salts undergo the ring-opening reaction upon treatment with methoxide anion .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported several methods for the preparation of a wide variety of 1-phenyl-1-benzothiophenium salts and demonstrated the stability of the sulfonium moiety sufficiently to investigate the chemistry of 1-benzothiophenium ion. , The triflate salt of 1-phenyl-1-benzothiophenium ion shows the tetrahedral structure around the sulfur atom with the phenyl group being out of the plane and the large bond alternation 8e. The short C(2)−C(3) bond length of 1.308 Å is much shorter than the corresponding values of 1-benzothiophene (1.354 Å, calculated value), 5-bromo-2,3-dimethyl-1-benzothiophene (1.355 Å), thiophene (1.369 Å) and 2-methyl-1-benzothiophene (1.382 Å) …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several papers have been published on the synthesis of S -alkyl- or S -arylthiophenium salts, and some of these compounds have known to be present among electrophilic alkylation or arylation reagents toward aromatics and heteroaromatics. However, in contrast to the chemistry of benzothiophenes, synthetic investigations of thiophenium as well as selenophenium still remain limited.…”
mentioning
confidence: 99%